BATU SEBAGAI SIMBOL KEHIDUPAN - Aindri Putri; Yusron Wikarya (Universitas Negeri Padang, 2020)
The purpose of making this final work is to visualize the stone through the abstract style of expressionism, asking everyone to learn or be motivated from nature, one of which are considered as inanimate and hard objects. The method of making works through several stages: preparation, elaboration, synthesis, concept preparation, finaly through exhibition, documentation and report making. The artwork presented was a symbol of human life on the rock. The ten that were titled hollow stones, stones arranged, stones dimples, boulder, coral reef, pumice stones, agate, bricks, gemstones and limestone.Kata kunci: Batu, Simbol, Kehidupan